2019
DOI: 10.1094/pdis-02-19-0360-re
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Beet Necrotic Yellow Vein Virus Strains in North Dakota and Minnesota

Abstract: Beet necrotic yellow vein virus (BNYVV) is the causal agent of rhizomania, a disease of global importance to the sugar beet industry. The most widely implemented resistance gene to rhizomania to date is Rz1, but resistance has been circumvented by resistance-breaking (RB) isolates worldwide. In an effort to gain greater understanding of the distribution of BNYVV and the nature of RB isolates in Minnesota and eastern North Dakota, sugar beet plants were grown in 594 soil samples obtained from production fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Furthermore, the variability in absorbance values between AYPR, VCHG, and VLHG suggests that the tetrad variants are associated with a different fitness advantage in the resistant genotype. This might be an explanation for the large variability of different tetrad variants found in natural virus populations (Galein et al, 2018;Weiland et al, 2019), which is also indicative for an ongoing virus evolution. The replacement of the RNA3 in the non-resistance-breaking BNYVV clone by an RNA3 derived from a resistance-breaking virus population demonstrated that two A-type populations can exchange genome components leading to infectious reassortments overcoming Rz1 resistance.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the variability in absorbance values between AYPR, VCHG, and VLHG suggests that the tetrad variants are associated with a different fitness advantage in the resistant genotype. This might be an explanation for the large variability of different tetrad variants found in natural virus populations (Galein et al, 2018;Weiland et al, 2019), which is also indicative for an ongoing virus evolution. The replacement of the RNA3 in the non-resistance-breaking BNYVV clone by an RNA3 derived from a resistance-breaking virus population demonstrated that two A-type populations can exchange genome components leading to infectious reassortments overcoming Rz1 resistance.…”
Section: Discussionmentioning
confidence: 91%
“…The most variable region of the BNYVV genome worldwide is the noted “tetrad region” encoded on RNA3 between nucleotides 645 and 656 (E12 strain, NCBI Accession #EU330455.1; [ 5 ]). The most common tetrad amino acids (AAs) observed in the samples of the present study included VCHG, ACHG, VLHG, and TLHG, the first three of which have a prior association with the breaking of Rz1-gene-based resistance in sugar beet [ 5 , 14 , 17 ]. All sequences were used to confirm the placement of the BNYVV-US within phylogenetic groupings ( Figure 2 ) previously reported by Chiba et al [ 25 ], Schirmer et al [ 34 ], and Zhuo et al [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…An exception to this observation worldwide is nucleotides encoding the “tetrad” of AAs within the p25 protein produced from RNA 3. The nucleotides at this location are considered to be among the most hypervariable within all eukaryotic viruses [ 25 , 34 , 43 ], a feature observed in our own recent study [ 17 ]. Moreover, recent associative [ 16 , 17 , 34 ] and functional [ 5 , 44 ] evidence suggests that variability in this region may account for the ability for some strains of the virus to circumvent dominant resistance genes in the sugar beet crop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations